Multidimensional Symptom Burden among Patients with Hemodialysis in Indonesia - Hinin Wasilah; Dhea Natashia; Chen- Hui Huang; Hsing- Mei Chen; Miaofen Yen (Jurnal Keperawatan Padjadjaran, 2021)
Background: Patients with hemodialysis commonly experience multiple symptoms. Most of the previous studies analyzed the symptoms as one dimension such as the severity dimension. Conducting the comprehensive symptom assessment among patients with hemodialysis is necessary to gain a better understanding of the symptom burden. Purpose: The aim of this study was to identify symptom burden among patients with hemodialysis comprehensively. Methods: This study was a descriptive study. A convenience sample of 320 patients undergoing hemodialysis was recruited from the dialysis units at two referral hospitals in Indonesia (Fatmawati Hospital and Cipto Mangunkusumo National Hospital). Indonesian Version of Chronic Kidney Disease – Symptom Burden Index (CKD-SBI) was used. For the data analysis, descriptive analysis was used. Results: Total 320 subjects were collected. This study found that lack of energy was the highest physical symptom burden under 4 dimensions: occurrence 269 (84.0%), severity (mean = 4.28, SD = 3.08), distress (mean = 4.42, SD = 3.09), and frequency (mean = 4.41, SD = 3.27). Furthermore, decreased interest in sex was the highest psychological symptom burden under for dimensions: occurrence 210 (65.6%), severity (mean = 3.39, SD = 3.38), distress (mean = 2.92, SD = 2.99), frequency (mean = 3.70, SD = 3.65). Conclusion: Lack of energy and decreased interest in sex were consistently the highest symptom burden among patients with hemodialysis. Creating appropriate interventions and managing the symptoms experienced by patients with hemodialysis comprehensively is very important to improve their quality of life.